Human iPS cell-derived cardiac tissue sheets for functional restoration of infarcted porcine hearts. - Masanosuke Ishigami; Hidetoshi Masumoto; Takeshi Ikuno; Takayuki Aoki; Masahide Kawatou; Kenji Minakata; Tadashi Ikeda; Ryuzo Sakata; Jun K Yamashita; Kenji Minatoya (PLoS ONE, 2018)
To realize human induced pluripotent stem cell (hiPSC)-based cardiac regenerative therapy, evidence of therapeutic advantages in human-sized diseased hearts are indispensable. In combination with an efficient and simultaneous differentiation of various cardiac lineages from hiPSCs and cell sheet technology, we aimed to generate clinical-sized large cardiac tissue sheets (L-CTSs) and to evaluate the therapeutic potential in porcine infarct heart. We simultaneously induced cardiomyocytes (CMs) and vascular cells [vascular endothelial cells (ECs) and vascular mural cells (MCs)] from hiPSCs. We generated L-CTSs using 10cm-sized temperature-responsive culture dishes. We induced myocardial infarction (MI) in micromini-pigs (15-25 kg) and transplanted the L-CTSs (Tx) 2 weeks after MI induction (4 sheets/recipient) under immunosuppression (Tx: n = 5, Sham: n = 5). Self-pulsating L-CTSs were approximately 3.5cm in diameter with 6.8×106±0.8 of cells containing cTnT+-CMs (45.6±13.2%), VE-cadherin+-ECs (5.3±4.4%) and PDGFRβ+-MCs (14.4±20.7%), respectively (n = 5). In Tx group, echocardiogram indicated a significantly higher systolic function of the left ventricle (LV) compared to that in sham control (Sham vs Tx: fractional shortening: 24.2±8.6 vs 40.5±9.7%; p<0.05). Ejection fraction evaluated by left ventriculogram was significantly higher in Tx group (25.3±6.2% vs 39.8±4.2%; p<0.01). Speckle tracking echocardiogram showed a significant increase of circumference strain in infarct and border regions after transplantation. Fibrotic area was significantly lower in Tx group (23.8±4.5 vs 15.9±3.8%; P<0.001). Capillary density in the border region was significantly higher in Tx group (75.9±42.6/mm2 vs 137.4±44.8/mm2, p<0.001). These data indicate that the L-CTS transplantation attenuated LV remodeling. L-CTSs potentially restore cardiac dysfunction of human-sized infarct heart.